ifo World Economic Survey August 2017 - Dorine Boumans; Christoph Zeiner; Marc Stöckli (ifo World Economic Survey, 2017)
World Economic Climate: ifo World Economic Climate Remains Positive - Advanced Economies: Advanced Economies Stabilise at a Favourable Level - Emerging and Developing Economies: Emerging and Developing Economies Project Slower Recovery - Special Box: A Comparison between CPB World Trade Monitor and the WES Indicator for Trade Volumes - Special Topic: The WES Special Question: Economic Inequality around the World
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies